Best Answer

( 8x2 - 14x - 30 ) divided by ( 2x - 6 ) = 4x + 5

Lvl 1

( 8x2 - 14x - 30 ) divided by ( 2x - 6 ) = 4x + 5

Lvl 1

Idont no

Lvl 1

( 48 - 14x ) divided by ( 2x - 6 ) = 4x + 5

Lvl 1

(16-14x-30)/2x-6 is (-14-14x)/2x-6. So (14x-14)/2x-6=(the answer)

Lvl 1

bru|-| l3$$ b3 frrr the r3@l qu3st10n b3 y@g@ z@ on y0 or /\/1c or c0

More answers

Lvl 5

(8x^2-14x-30)/(2x-6)=(4x^2-x-15)/(x-3)=(4x+5)(x-3)/9x-3) =(4x+5)

Q: 8x2 - 14x - 30 by 2x - 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Calculus

Substitute 2x - 6 for y in first equation: 12x - 5(2x - 6) = 30 ie 12x - 10x + 30 = 30 so 2x = 0 making x = 0 and y = -6

You can answer this by the method of substitution, which means that you find what one variable equals and you substitute it into the second equation to find the other variable.14x-2y=78; solve for y-2y=78-14x; subtract 14x on both sidesy=-39+7x; divide both sides by -2y=7x-39Substitute 7x-39 for y in the second equation.2x-2(7x-39)=6; solve for x2x-14x+78=6; distribute the -2-12x+78=6-12x=-72; subtract 78 on both sidesx=6; divide both sides by -12Now go back to the first equation and for x, substitute 6. You can either substitute in 14x-2y=78 or the y=7x-39, but it's easier where you already have y isolated.y=7(6)-39y=42-39y=3You got that x=6 and that y=3; therefore, the ordered pair is (6,3).

2x-6=4 6+4=2x 10=2x 10/2=x 5=x x=5

2x + 4 = 10 2x = 10 - 4 = 6 2x = 6 x = 6/2 = 3

2x + 6 = what? There is not enough information to solve for x.

Related questions

Collect terms. Constants with constants, variables with matching variables. 6 is a constant, and the rest are all x terms. 6 - 2x - 14x 6 + (-2x -14x) 6 + (-16x) 6 - 16x ■

6+(-2x-8)-(-3+12x)-(4y)= 6-2x-8+3-12x-4y=1-14x-4y 1-14x=4y (1-14x)/4=y

5x-8= -2x+6(+8 = +8)5x=-2x+14(+2x = +2x)7x=14x=14

6x2 + 14x -12 = (3x - 2) (2x + 6). There they are.

are those two different problems ? ... i am going to solve them as if they are 14x-2y=78 (re arange the terms to be easily solved) -2y=78-14x (times by -1) 2y= -78+14x (divide all terms by 2) y=-39+7x (so) y=7x-39 2x-2y=6 (re arange the terms to be easily solved) -2y=6-2x (times by -1) 2y=2x-6 (divide all terms by 2) y=x-6

4x2 + 14x + 12 = 2(2x2 + 7x + 6) = 2(2x + 3)(x + 2)

14x + 6 = 6 14x + 6 - 6 = 6 - 6 14x = 0 14x / 14 = 0 / 14 x = 0

124 (?) Try to do it on the calculator on your computer * * * * * No, 4x2 + 14x + 12 is factorised, as follows: 4x2 + 14x + 12 = 2(2x2 + 7x + 6) = 2(x + 2)(2x + 3).

30-2x 6 x 5 = 30

x = 1.5 because -7x + 3 = -15/2 -14x + 6 = -15 (x2) -14x + 21 = 0 (+15) 21 = 14x (+14x) 3 = 2x (/7) 1.5 = x

4(2x - 3) + 3(2x + 2) 8x - 12 + 6x + 6 14x - 6

(3x - 2)(2x + 6) or 2(3x - 2)(x + 3)